201k views
13 votes
Rewrite the equations in the form ax^2+bx+c =0:
-5x (x +6)=4(x-3) -10
4x^2-2x(3x+1)=5

User Kokito
by
4.9k points

2 Answers

9 votes

Final answer:

The two equations given can be expanded and terms combined to rewrite them in the standard quadratic form ax^2 + bx + c = 0. The first becomes -5x^2 - 34x + 22 = 0 and the second is -2x^2 - 2x - 5 = 0. The quadratic formula can then be applied to solve for x.

Step-by-step explanation:

To rewrite the given equations in the standard form ax^2 + bx + c = 0, we need to expand and combine like terms and move all terms to one side of the equation to set it equal to zero.

The first equation is:

-5x(x + 6) = 4(x - 3) - 10.

Expanding both sides we get:

-5x^2 - 30x = 4x - 12 - 10.

Now, bring all terms to one side:

-5x^2 - 30x - 4x + 12 + 10 = 0.

Combine like terms:

-5x^2 - 34x + 22 = 0.

The second equation is:

4x^2 - 2x(3x + 1) = 5.

Expanding the left side we get:

4x^2 - 6x^2 - 2x = 5.

Combine like terms and subtract 5 from both sides:

-2x^2 - 2x - 5 = 0.

The rewritten equations in the standard form are:
-5x^2 - 34x + 22 = 0 and -2x^2 - 2x - 5 = 0.

Solving these equations can be done using the quadratic formula, which is useful for equations in this standard form.

User Ismael Sarmento
by
4.8k points
3 votes

Step-by-step explanation:

this is my answer...sorry if I made any mistake

Rewrite the equations in the form ax^2+bx+c =0: -5x (x +6)=4(x-3) -10 4x^2-2x(3x+1)=5-example-1
User Vadim Novozhilov
by
5.1k points